ENVIRONMENTAL PERCEPTION OLD PEIRÓPOLIS RESIDENTS, UBERABA, MG: REFLECTIONS RELEVANT TO SUSTAINABILITY - Motta Palermo, Pedro; Tambellini, Mariângela (Revista Desenvolvimento Social, 2020)
Especially due to the impacts of agricultural and livestock activities in the Cerrado regions are important studies related to Human Ecology. On these studies, we believe are necessary not only raising sustainable behaviors and activities, as well as the observation of aspects of human subjectivity. The Peirópolis-MG neighborhood is frequented due to environmental tourist attractions and paleontological. Older residents of the neighborhood were using available resources of flora as medicines and food, especially in the manufacture of homemade candy. Even today Peirópolis candy are known and sold, but the ingredients are not produced locally. This study aimed to identify perceptions about changes in the environment and society arising from the neighborhood urbanization process. Prior visits were carried out to know the place and the people. From this it selected a group of six women, because they are old residents of the neighborhood and because he has or had activities related to the use of natural resources. The interviews revealed the importance attributed to intensive agriculture as a factor responsible for changes in the neighborhood in recent years, evaluated negatively. The urbanization resulting from tourist activities was assessed as positive or negative impact on the community.